Hate speech as disfunction of an evolving encyclopedia. Reconsidering discursive injustice from the perspective of a logic of culture - Gasparini, Andrea (Rivista Italiana di Filosofia del Linguaggio, 2023)
Claudia Bianchi’s work in the last years focuses on hate speech, which she approaches from the point of view of the theory of the speech acts. She proposes the concept of discursive injustice, with the aim of safeguarding the authority and the responsibilities of both the hearers and the speakers. Bianchi claims that an illocutionary act is happily performed when the speaker has done what is necessary to secure the uptake, according to her intentions and conventional procedures. In this paper I propose to explain the conventionality of the ordinary speech acts through the circumstantial elements given by the social frame and the cultural network of shared meanings. To this purpose I take advantage of the reflection of the sociologist Pierre Bourdieu and of the concept of encyclopedia elaborated by the semiologist Umberto Eco. I show that it is not easy to talk about the authority of the speakers and hearers and about shared conventions inside a culture. What is possible or expected to do with words is tightly linked with sociological and cultural factors, such as the evolution of the encyclopedia, which explains the contradictions pointed out by hate speech.